New species of Chaetozone and Tharyx (Polychaeta: Cirratulidae) from the Alaskan and Canadian Arctic and the Northeastern Pacific, including a description of the lectotype of Chaetozone setosa Malmgren from Spitsbergen in the Norwegian Arctic - Blake, James A. (Zootaxa, 2015)
Eight new species of cirratulid polychaetes of the genus Chaetozone from the Alaskan (Beaufort Sea) and Canadian Arctic (Baffin Island, Baffin Bay, Labrador, Hudson Strait, and Hudson Bay) and the Northeastern Pacific are reported together with two new species of Tharyx from the Alaskan Beaufort Sea and the Strait of Juan de Fuca. The new species of Chaetozone and Tharyx are compared with related species; distinct species groups within these genera are discussed. A redescription of C. setosa Malmgren, 1867, the type species of the genus from Spitsbergen, based on a lectotype and associated paralectotypes designated by the late Dr. Mary E. Petersen is presented. A review of characters important in the taxonomy of the genera Chaetozone and Tharyx is presented. A key to species of Chaetozone from the Northeastern Pacific and North American Arctic is provided.